Mikale Instant Porridge's Formulation and Acceptability As a Complementary Breast Milk - Imelda Telisa; Hana Martinah Putri; Terati Terati; Yuli Hartati; Arif Dwisetyo Haripamilu (Jurnal Gizi Prima (Prime Nutrition Journal), 2024)
Background: The quality of human resources can be impacted by nutritional status. A condition known as lack of protein energy occurs when a person consumes insufficient amounts of nutrient-rich food to meet their needs. Supplementary food for breast milk that is high in energy and protein is one way to ensure that children receive a healthy diet, especially those aged 6 to 24 months.Research Purposes: This research aims to determine the formulation, acceptability, and analysis of the dietary fiber and macronutrient content (protein and carbohydrates) in MiKaLe instant porridge. Research Methods: This research method is an experimental study using a completely randomized design (CRD) that is non-factorial, with 35 panelists who are organoleptic test subjects and three formulations. Research Result: The results of the organoleptic test indicated that the chosen MiKaLe instant porridge, made with 15 grams of yellow millet flour, 25 grams of catfish flour, and 20 grams of soybean flour, was formula 1 (F1). Based on the Comstock acceptability test results, 90% of children left less than 50% of the product, and 10% left more than 75%. The product's nutritional facts state that every 100 grams has 397.99 kcal of energy, 18.52% protein, 14.55% fat, 48.24% carbs, and 16.60% dietary fiber. According to the Friedman test, there is a correlation between color, aroma, flavor, and texture. Conclusion: The results of this research indicate that instant MiKaLe porridge is suitable for breast milk substitutes for infants between the ages of six and eleven months.